First episode of psychiatric and neuropsychiatric disease among patients infected with COVID‐19: A scoping review - Wali Yousufzai; Alex Heo; Kyle Gu; Edward Sun; Gabriel Lopez; Shreya Balamurali; Jennifer Adjei‐Mosi; Riley Shin; Daniel B. Stuart; Peggy Edwards; Regina Baronia; Wail Amor; et al. (PCN Reports, 2025)
Abstract This scoping review aims to examine the frequency and prevalence of neuropsychiatric disorders reported in patients infected with coronavirus disease 2019, and the mechanisms by which these develop during and post infection. A systematic search using relevant search terms and key words was done on six electronic databases of literature on neuropsychiatric conditions post‐coronavirus disease 2019 infection from 2020 to 2023. Data were extracted following Joanna Briggs Institute guidelines, focusing on key findings, intervention details, and outcomes. We included 333 studies in the review. Studies indicated an elevated risk of neuropsychiatric disorders post‐coronavirus disease 2019, with some risks remaining high 2 years after diagnosis. A significant prevalence of depressive, psychotic, and anxiety disorders, as well as post‐traumatic stress symptoms were noted among coronavirus disease 2019 survivors. There was increased prevalence of insomnia and other sleep disturbances, mild to severe cognitive dysfunction, and eating disorders. Coronavirus disease 2019 infection is associated with a significant risk of developing various neuropsychiatric disorders, including schizophrenia, depressive disorders, anxiety, post‐traumatic stress disorder, and cognitive dysfunction. Long‐term monitoring and early interventions are essential to mitigate these risks and improve patient outcomes.